(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Data has become a crucial component in the digital age that dictates decision-making, innovation, and competitive edge in many industries. There is a long-standing practice of examining, or analyzing raw data to identify significant patterns and trends in data analytics, but in recent years, it has become more than just an adjunct or supportive role and has become a critical driver of transformation. This paper highlights the growing impacts of data analytics and how it has permeated many sectors, including, but not limited to, healthcare, finance, manufacturing, education, and government. We introduce and describe three types of analytics, current trends in predictive analytics, prescriptive analytics, and real-time analytics, along with the recent emergence of new technologies such as artificial intelligence (AI), machine learning (ML), and cloud computing. This paper also discusses some challenges of data analytics such as data use and privacy and security and ethical issues that we need to overcome to realize its full potential. Finally, by looking at the future data analytics holds for us, we indicate how data-driven strategies will continue to change industries, job roles, and global competitiveness over the future decades.